2019
DOI: 10.7554/elife.43059
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically aggregation-prone proteins form amyloid-like aggregates and contribute to tissue aging in Caenorhabditis elegans

Abstract: Reduced protein homeostasis leading to increased protein instability is a common molecular feature of aging, but it remains unclear whether this is a cause or consequence of the aging process. In neurodegenerative diseases and other amyloidoses, specific proteins self-assemble into amyloid fibrils and accumulate as pathological aggregates in different tissues. More recently, widespread protein aggregation has been described during normal aging. Until now, an extensive characterization of the nature of age-depe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
80
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(88 citation statements)
references
References 73 publications
8
80
0
Order By: Relevance
“…Recent studies have shown that protein aggregation accelerates the functional decline of different tissues [49]. In support of this idea, we detected a marked increase in protein aggregation in lung fibroblasts of IPF and chronically injured mice and this finding was associated with increases in cellular senescence and myofibroblast activation markers.…”
Section: Discussionsupporting
confidence: 88%
“…Recent studies have shown that protein aggregation accelerates the functional decline of different tissues [49]. In support of this idea, we detected a marked increase in protein aggregation in lung fibroblasts of IPF and chronically injured mice and this finding was associated with increases in cellular senescence and myofibroblast activation markers.…”
Section: Discussionsupporting
confidence: 88%
“…Of note, the core region of some large aggregates was refractory to photoconversion ( Fig. 2 and as previously described [22]). Thereafter, we followed the rate of new (green emitting) aggregate formation and the rate of old (red emitting) aggregate removal over time.…”
Section: Sapa Prevents De Novo Formation Of Aggregatessupporting
confidence: 71%
“…PAB-1 contains a low complexity prion-like domain and undergoes liquid-liquid phase separation to form stress granules, putting it at risk of aggregating during aging or chronic stress in C. elegans [23,38]. In contrast, both KIN-19 and RHO-1 are highly structured globular proteins, which are intrinsically prone to aggregate shortly after synthesis [22]. Notably, the divergent aggregation processes are controlled by different mechanisms [23,38,39].…”
Section: Sapa Displays Aggregation-prone Substrate Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…FUS501 aggregation may also promote aggregation of other proteins. It is well established that the C. elegans intracellular environment becomes more prone to aggregation across ageing, and this is exacerbated by the overexpression of aggregation-prone proteins (David et al, 2010; Huang et al, 2019; Walther et al, 2015).…”
Section: Discussionmentioning
confidence: 99%